1998
DOI: 10.1266/ggs.73.345
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of the copia-like retrotransposable element Yokozuna on the W chromosome of the silkworm, Bombyx mori.

Abstract: We discovered a novel retrotransposable element, designated Yokozuna, on the W chromosome of Bombyx mori. The size of this element is 4738 bp, including a 208-bp long terminal repeat (LTR) on one side and a 183-bp LTR on the other. This retrotransposable element is flanked by a 5-bp target site duplication, TAATT. Yokozuna contains a single long open reading frame (ORF) and the whole deduced amino acid sequence of ORF reveals strong homology with copia of Drosophila. Moreover, an alignment analysis of the reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…In some species, such as E. kuehniella and G. mellonella, the W-specific sequences predominate, whereas this fraction is barely noticeable in the W chromatin of B. mori (Sahara et al 2003a). The latter finding is in agreement with the difficulty of isolating DNA fragments from the W chromosome of B. mori; the few that were recovered contained transposons (Abe et al , 2000Ohbayashi et al 1998). Recently, Sahara et al (2003b) demonstrated the identification of the W chromosome in B. mori using fluorescence in situ hybridization (FISH) with W-chromosome-derived bacterial artificial chromosome (BAC) probes.…”
Section: Introductionsupporting
confidence: 67%
“…In some species, such as E. kuehniella and G. mellonella, the W-specific sequences predominate, whereas this fraction is barely noticeable in the W chromatin of B. mori (Sahara et al 2003a). The latter finding is in agreement with the difficulty of isolating DNA fragments from the W chromosome of B. mori; the few that were recovered contained transposons (Abe et al , 2000Ohbayashi et al 1998). Recently, Sahara et al (2003b) demonstrated the identification of the W chromosome in B. mori using fluorescence in situ hybridization (FISH) with W-chromosome-derived bacterial artificial chromosome (BAC) probes.…”
Section: Introductionsupporting
confidence: 67%
“…The heterochromatin of holocentric chromosomes, therefore, shows several common features with that of monocentric chromosomes since both contain ATrich satellite DNAs, transposable elements, HP1 proteins and methylated histones (e.g. Ohbayashi et al, 1998;Mandrioli et al, 1999;Cowell et al, 2002;Mandrioli, 2002;Mandrioli, 2003a, b;Mandrioli et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…From these libraries, we obtained three lambda phage clones containing the W-Kabuki, W-Samurai and W-Yamato RAPD sequences by PCR amplification and sequencing. These DNA sequences comprise the nested structures of many retrotransposable elements (Ohbayashi et al, 1998;Abe et al, 2000Abe et al, , 2002, and manuscript in preparation).…”
Section: Identification Of the Rapd Markers On The W Chromosomementioning
confidence: 99%